Relações interorganizacionais, competências e resultados de inovação em organizações industriais - Machado, Augusto Cesar Marins (2015)
The present study is to identify the influence of interorganizational relations in the development of organizational competence of innovation and innovation results in industrial organizations. The predominant theoretical approach at work is supported by the Resource Based View (RBV), considering the analytical categories of study as strategic resources to the organization and when mobilized, coordinated and delivered, ensure organizational performance. The empirical field research was applied to the manufacturing industries of the state of Paraná participants Innovation Compass Program, an initiative of the National Service of Industrial Education of Paraná (SENAI / PR). We chose to have the sample of 1,240 respondents thesis all industries Innovation Compass by having an overview, allows them to have study suggestions and practical recommendations that can be accessed and used by all sectors, respecting the specificities sectoral, regional and possession. The makers of public and private policies related to innovation in industries can benefit from a description and integrated analysis of all sectors due to breadth, scope and systemic view of the analytical categories made by this thesis. The results of this study indicate that there is a positive and significant relationship between the following hypotheses: (i) inter-organizational relationships and organizational competence of innovation; (ii) organizational competence of innovation and the results of innovation; and (iii) inter-relationships and the results of innovation. Only the last hypothesis of the study was not found: there is positive and significant relationship between the interorganizational relations and the results of innovation, moderated by the organizational competence of innovation.